Effect of fat source on performance and carcass quality of finishing steers - Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials that utilized 356 steers were conducted to evaluate the effects of various fat sources (3.596 of ration dry matter) on performance and carcass traits of finishing cattle fed flaked milo diets. In trial 1, soybean oil, bleachable tallow, and yellow grease (blend of tallow and restaurant grease) were compared to a nonfat control. Feeding fat increased (P<.05) daily gain, feed efficiency, carcass weight, and dressing percent of steers. Soybean oil and yellow grease also tended to increase 12th rib backfat thickness and marbling. Feed costs of gain were improved only by yellow grease. However, when increased carcass yield and quality were considered, there was a significant economic return from all fat sources. In trial 2, fat treatments were acidulated soybean soapstock (SBSS), tallow, a blend of 7096 SBSS:3096 tallow, and yellow grease. Feeding tallow or the SBSS: tallow blend improved (P<.05) feed efficiency by 7.796 compared to the nonfat control. Pooled across source, feeding fat increased (P<.10) backfat thickness and marbling. Compared to the control, feed cost of gain was reduced 6 cents/l b by the SBSS:tallow blend. However, when increased carcass value was accounted for, net returns of $3.50 to $6.00 per head were seen for SBSS, tallow, and SBSS:tallow priced at 13, 17, and 13 cents per lb, respectively. The SBSS:tallow blend provided greater performance than was predicted by observed performance of steers fed SBSS or tallow separately, an indication of associative response. In trial 2, intake and gain were lowest for yellow grease, resulting in a negative economic return, which is in complete disagreement with results obtained in trial 1.
Keywords: Beef; Performance; Carcass quality; Finishing steers